2006
DOI: 10.1007/s00439-006-0141-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel functional variants of the melanocortin 1 receptor gene originated from Asians

Abstract: Human melanocortin 1 receptor (MC1R) is a seven transmembrane G-coupled protein receptor that upregulates the cAMP pathway. Several functional variants of MC1R that show an impaired ability to activate the cAMP pathway are strongly associated with fair skin and red hair in Europeans and European descendants. The sequence variations of the MC1R gene were repeatedly investigated against worldwide populations; however, there was no evidence that functional variant of MC1R exists in non-European descendants. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 45 publications
3
44
0
1
Order By: Relevance
“…However, an in vitro study showed that the 92M allele caused impaired MC1R function; in contrast, the 163Q allele had almost the same response to a-melanocyte simulation hormone as the human consensus allele. 32 These results may explain the difference in the effect of the V92M and R163Q alleles on skin pigmentation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, an in vitro study showed that the 92M allele caused impaired MC1R function; in contrast, the 163Q allele had almost the same response to a-melanocyte simulation hormone as the human consensus allele. 32 These results may explain the difference in the effect of the V92M and R163Q alleles on skin pigmentation.…”
Section: Discussionmentioning
confidence: 97%
“…An in vitro study on the function of MC1R variants also indicates that 163Q functions normally when compared with the consensus. 32 Motokawa et al 68 investigated polymorphisms in the promoter region of MC1R linked to R163Q among 247 Japanese. They found that the promoter haplotypes with a combination of À490T, À445A and À226T, 98.5% of which bore the 163Q allele in the coding region, showed lower OR for initiating freckles and solar lentigines than did the human consensus haplotype ( À490C, À445G, À226A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MC1R is a very small gene of less than 1 kb in size, which lacks any introns, thus being attractive for direct DNA sequencing to unveil pigmentation associated or causing DNA variants. Non-synonymous variants in MC1R were found to be nearly absent in Africans but highly enriched in Europeans and Asians [105][106][107][108]. Nine DNA variants, V60L (rs1805005), D84E (rs1805006), R151C (rs1805007), I155T (rs1110440), R160W (rs1805008), R163Q (rs885479), R142H (rs11547464), D294H (rs1805009), and V92M (rs2228479), are common in Europeans, and two DNA variants, A163G and V92M, are common in Asians [106,109].…”
Section: Mc1r and Asipmentioning
confidence: 99%
“…The study of RHC MC1R variants provided information about their association with other phenotypes and their effect on functioning of MSH-R has extended its role beyond pigmentation to diseased phenotypes. The MC1R variants, mainly the RHC alleles were also reported to be associated with increased risk of various types of melanoma [41] and UV induced susceptibility to skin damage [42]. The MC1R variants have been reported to be associated with pigmentary disorders including vitiligo [43], severe photoaging [44], congenital melanocytic nevi [45] and OCA [46].…”
Section: Oca6mentioning
confidence: 99%